Skeletown : Sí. ¡No! - Montijo, Rhode (Montijo, Rhode. Skeletown (Series), 2023)
"Skeleton-like characters inspired by Día de los Muertos engage in "good" and "bad" behavior in a humorous exploration of opposites" -- Provided by publisher.